Testing an integrative work-study conflict and enrichment model - Andrade, Cláudia (Pensando Psicología, 2017)
Purpose: The article aims to test, using structural equations, a work-study relationship conflict and enrichment background model.Method: 87 students-workers of a bachelor’s degree, of both sexes (24 men and 63 women), participated.Results: The number of working hours and academic self-efficacy are related to the work-study conflict. Peer support and academic self-efficacy stem from workstudy enrichment. As might be expected, both work-study conflict and enrichment are related to satisfaction with academic development.Conclusion: Given that higher education institutions aim to increasingly provide lifelong learning to a student population that reconciles studies with work, it is important to deepen the understanding of how work can influence study negatively and positively, in order to guide informed decisions for students and promote more inclusive educational practices
Keywords: work-study conflict; work-study enrichment; higher education students; work